Comparison of Post-Operative Analgesic Effects of Intrathecal Dexmeditomidine Versus Intrathecal Ketamine Added to Bupivacaine in Total Knee Replacement Surgeries - Hasnain, Fahad; Saeed, Munim; Shah, Syed Qasim Ali; Riaz, Muhammad Mohsin; Khalil, Waqas; Sharif, Muhammad Huzaifa (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the analgesic efficacy of Dexmedetomidine versus Ketamine when added to intrathecal Bupivacaine in patients undergoing unilateral total knee replacement surgery. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anesthesia, Combined Military Hospital, Rawalpindi, Pakistan, from May to Oct 2022. Methodology: Our study enrolled a total of 80 patients, divided into Dexmedetomidine group (n=40) and Ketamine group (n=40) group using non-probability consecutive sampling. Patients in both groups received 2.5 ml of 0.5% Bupivacaine with Dexmedetomidine group receiving 5 mcg (0.5 ml) of the drug and Ketamine group 0.1 mg/kg of Ketamine in 0.5 ml to a total volume of 3 ml. Data analysis was performed using SPSS 26.0, with significance set at p≤0.05. Results: Time of onset for sensory block in Dexmedetomidine group was delayed than Ketamine group with mean time of onset 4.34±0.14 minutes versus 3.38±0.10 minutes (p<0.0001). The duration of block was more for Ketamine group with mean time of 326.20±12.67 minutes versus 243.76±2.54 minutes (p<0.0001). When comparing motor blockade, the time of onset to successfully reach Bromage Score 3 was similarly delayed in Dexmedetomidine group with mean time of onset 3.33±0.12 minutes versus 2.36±0.09 minutes (p<0.0001). A similar trend was seen in duration of block with mean time 203.40±1.46 minutes versus 263.01±13.44 minutes (p<0.0001) Conclusion: Ketamine provided superior analgesia, block onset and duration with less post-operative analgesia requirement.